2013
DOI: 10.1186/1471-2458-13-111
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HPV vaccination intentions among Dutch girls and their mothers: a cross-sectional study

Abstract: BackgroundThe Dutch government recently added universal Human Papilloma Virus (HPV) vaccination for 12-year-old girls to the existing national immunization program. The participation rate for the initial catch-up campaign for girls aged 13 to 16 years in 2009 was lower (47%) than expected (70%). To inform future HPV information campaigns, this paper examines the social and psychological determinants of the HPV vaccination intentions of girls aged 13 to 16 years and their mothers who were targeted by the Dutch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
5
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(133 citation statements)
references
References 44 publications
12
111
5
5
Order By: Relevance
“…Power analysis showed that a minimal sample size of 32 participants per condition was needed (with power = 0.80, and two-sided = 0.05; Hintze, 2004). We took into account an attrition rate of 30% and a response rate of 5%, based on previous experiences (Van Keulen et al, 2013). Consequently, 3,680 mothers were invited.…”
Section: Required Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Power analysis showed that a minimal sample size of 32 participants per condition was needed (with power = 0.80, and two-sided = 0.05; Hintze, 2004). We took into account an attrition rate of 30% and a response rate of 5%, based on previous experiences (Van Keulen et al, 2013). Consequently, 3,680 mothers were invited.…”
Section: Required Sample Sizementioning
confidence: 99%
“…Several studies have provided insight in factors constituting HPV-vaccination acceptability (e.g., Alberts et al, 2017;Hofman et al, 2014;Pot et al, 2017;Van Keulen et al, 2013). Results from two Dutch studies among mothers of girls to-be-invited showed that 'modifiable' social-psychological determinants (e.g., perceived daughters' susceptibility towards HPV-related risks) accounted for large proportions of variance in HPV-vaccination intention (Van Keulen et al, 2013;Pot et al, 2017). Mothers' intention, in turn, was found to be the main and stable predictor of their daughters' actual uptake (Pot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to an increased investment in risk communication skills and more attention paid to the role of social media (van Keulen et al . ). Once again, this points to a lasting transformative effect of the vaccine on the infrastructure.…”
Section: New Vaccines and Old Infrastructures: Creating A ‘Good Enougmentioning
confidence: 97%
“…Government, regulatory bodies and development partners have adopted different vaccination models that aim to ensure smooth uninterrupted administration of the three approved vaccine dosages for the eligible population with high acceptability . For instance, some developed countries incorporated HPV vaccination into their national immunization program with health insurance coverage, whereas others make eligible subjects pay for the vaccine . In most developing countries, the Global Alliance for Vaccine Immunisation (GAVI) has championed the course of cost‐reduction and access for vaccines, such as the HPV vaccine, to the population at risk .…”
Section: Introductionmentioning
confidence: 99%